Analisis Efektivitas Penggunaan Quick Response Code Indonesian Standard (QRIS) sebagai Alat Pembayaran Non Tunai pada Bank Syariah Indonesia KCP Godean 2 - Putri, Sulistiani Arianti; Rahmanto, Dhidhin Noer Ady (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Sulistiani Arianti Putri, Dhidhin Noer Ady Rahmanto Universitas Alma Ata Yogyakarta 192100137@almaata.ac.id ABSTRACT The purpose of this study was conducted to find out and examine how effective the use of the Quick Response Code Indonesian Standard (QRIS) feature at Bank Syariah Indonesia KCP Godean 2 is to use it as a non-cash payment instrument. This type of research is included in field research, which means explaining and describing conditions and phenomena more clearly related to the situation that occurs, therefore the type of research used is a type of qualitative research through interviews and documentation. The subjects in this study were Branch Managers, Consumer Branch Relations Managers, Funding and Transaction Staff, Customer Service and customers who use QRIS BSI KCP Godean 2. The results of this study indicate that the effectiveness of using QRIS as a non-cash payment tool has been running effectively, this is evidenced with the fulfillment of 3 aspects of effectiveness (source approach, process approach and target approach). Meanwhile, the performance effectiveness of Islamic banks in implementing QRIS shows the fulfillment of two of the three approaches, namely the source approach and the process approach. For one other measure of effectiveness, it is considered that it cannot be fulfilled, namely the target approach because it cannot achieve the results or outputs that have been previously set. The cause of BSI KCP Godean 2 not achieving results or output was the lack of availability of Human Resources (HR). Even so, statements from customers regarding service quality are quite good and satisfying. Keywords: Effectiveness, Usage, Performance, Standard Indonesian Quick Response Code